Ideological and Nihilistic Violence in Adolescents Referred to a Specialized Clinic for Violent Extremism - Rousseau, Cécile (Canadian journal of criminology and criminal justice, 2025)
Epidemiological surveys document changes in youth attitudes towards violence, but empirical data on clinical samples of adolescents involved in or at risk of ideologically motivated and nihilistic violence is surprisingly scarce, making it difficult to understand the risk and protective factors, as well as the specific clinical needs and characteristics of youth at risk of or involved in these forms of violent behaviors. This article uses a mixed-method concurrent triangulation design to combine quantitative data collected from the clinical files of clients referred to the Montreal Polarization team and qualitative data collected via a focus group with practitioners. It compares adolescents attracted by ideological and nihilistic violence (n = 58) with their adult counterparts (n = 66). Results show that nihilistic violence is more common in adolescents than in adults. In adolescents attracted by ideological and nihilistic violence, stress-related disorders are the most frequent diagnosis and family and school grievances are at the forefront of documented adversities. Intervention should privilege a grievance-based and trauma-informed approach to adolescents expressing their distress through violence, favouring reintegration and minimizing exclusion and stigmatization.